2009
DOI: 10.1002/ajh.21383
|View full text |Cite
|
Sign up to set email alerts
|

Persistent neutropenia in chronic myelogenous leukemia in chronic phase treated with imatinib mesylate

Abstract: A 48-year-old woman presented with left upper abdominal pain. Physical examination showed pallor and a 6-cm splenomegaly. The full blood count showed hemoglobin: 8.4 g/dL, white cell count: 144 3 10 9 /L, and platelet count: 982 3 10 9 /L. The blood smear showed a bimodal increase in myelocytes and neutrophils, with eosinophilia and basophilia. Bone marrow aspirate was markedly hypercellular with granulocytic hyperplasia and no increase in blasts. Megakaryocytes were small and hypolobated. Morphologic features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Administration of G‐CSF in patients B and C might have accelerated neutrophil regeneration . In patients with CML, G‐CSF has been shown to be effective in overcoming imatinib‐induced neutropenia . In this way, recovery of neutrophil counts can even be achieved during uninterrupted imatinib therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of G‐CSF in patients B and C might have accelerated neutrophil regeneration . In patients with CML, G‐CSF has been shown to be effective in overcoming imatinib‐induced neutropenia . In this way, recovery of neutrophil counts can even be achieved during uninterrupted imatinib therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced effectiveness of imatinib monotherapy beside its immunosuppressive action led to recurrent dose interruption and thus compromised patient outcome . Perhaps, combining anticancer drugs with natural micronutrients presents an advantage.…”
Section: Discussionmentioning
confidence: 99%
“…However, c‐kit mutation and over‐expression associated with pro‐angiogenic and anti‐apoptotic responses resulted in compromised imatinib cytotoxicity and development of imatinib‐resistant cancer cells . It has also been reported that 45% of imatinib‐treated patients experienced severe neutropenia requiring interruption of therapy or dose reduction ending in compromising patient outcome . Thereby, several reports have described reduced effectiveness of imatinib as single agent for successful chemotherapy .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As per Yu-Yan Hwang et al, persistent neutropenia was observed after imatinib treatment. [66] SAWYERS et al patients treated with 400 mg and 600 mg of imatinib, most common grade 4 abnormalities was neutropenia. [50] As per N. Singhal et al, neutropenia is the most common side effect of imatinib treatment.…”
Section: Neutrophilsmentioning
confidence: 99%